Peran Kepala Madrasah dalam Meningkatkan Prestasi Siswa Melalui Ekstrakurikuler Pramuka di MTs N 6 Kediri - Yusuf Khunaifi, A’an; Agustina Fahmi, Laila (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This research concerns the role of the madrasah head in improving student achievement through scout extracurriculars. In terms of improving student achievement, school principals provide a platform to develop their potential both in the areas of academic and non-academic achievement, including scouting. This research aims to find out the role of school principals in improving student achievement, the form of principal motivation and what are the supporting and inhibiting factors. Research problems include the role of the madrasah head in improving student achievement through extracurricular scouting, the form of motivation provided by the madrasah head and what are the supporting and inhibiting factors. This research is field research using qualitative methods. And data collection techniques through interviews, observation, and documentation. Then the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The result of the research are the role of the principal in improving student achievement through extracurricular scouting at MTsN 6 Kediri as an educator, leader, manager, motivation, and supervisor. The motivation given by the school principal is in the form of appreciation. The supporting factor is the cooperation of the school principal and all school members. The inhibiting factors are the change of madrasah heads and funding for each scouting event.